Impact of reconstruction parameters on spatial resolution and its comparison between cadmium-zinc-telluride SPECT/CT and conventional SPECT/CT. Issue 1 (January 2022) - Wang, Miao; Dong, Sheng; Zhang, Ruyi; Sun, Danyang; Wang, Shen; Shen, Yiming; Li, Ning; Wang, Peng; Tan, Jian; Meng, Zhaowei; Jia, Qiang
Abstract : Objective: To evaluate the impact of reconstruction parameters on the spatial resolution of the tomographic image in single photon emission computed tomography (SPECT)/computed tomography (CT), and compare spatial resolution between a new polyvalent whole-body Cadmium-Zinc-Telluride camera (CZT-SPECT/CT) and a conventional dual-head Anger camera (conventional SPECT/CT). Methods: Spatial resolution was evaluated with four-line sources filled with 99m Tc in tomographic images reconstructed by varying reconstruction parameters. Ordered-subset expectation maximization (OSEM) algorithm was performed with varying iterations (1–20), the number of subsets was fixed at 10. Butterworth filter, Gauss filter and no-filter were selected, respectively. Computed tomography-based attenuation correction (CTAC), scatter correction, resolution recovery and no correction (NC) were adopted for image correction. Filtered back projection (FBP) with Butterworth filter and CTAC was performed in image reconstruction. Spatial resolution was expressed by the full width at half-maximum (FWHM) value. Results: The impact of reconstruction parameters on the spatial resolution was identical in both cameras: FWHM values decreased with the increase of iterations and converged uniformly when the number of iterations was over 4. FWHM values decreased with the increase of cutoff frequency of the Butterworth filter and increased with the increase of the Gauss filter. scatter correction and resolution recovery improved spatial resolution, whereas CTAC had a negligible effect on spatial resolution when reconstructed by OSEM. FWHM was generally lower with OSEM reconstruction than FBP reconstruction. On the whole, under the same reconstruction conditions, CZT-SPECT/CT had a lower FWHM value than conventional SPECT/CT. Conclusion: The spatial resolution was improved with the increase of iterations. Increasing the cutoff frequency of the Butterworth filter and decreasing the Gauss filter enhanced spatial resolution. The spatial resolution was better reconstructed by OSEM associated with attenuation correction, scatter correction and resolution recovery than FBP. CZT-SPECT/CT had better spatial resolution than conventional SPECT/CT.